MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN MAKE A MATCH PADA PELAJARAN BAHASA INGGRIS DI KELAS IX-5 SMP NEGERI 2 TANJUNG MORAWA - Purba, Tambun (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
This research is aimed to improve activity and learning studentsâ result in studying english through an usage of learning model make a match. The subject of thisresearch is students of class IX-5 SMP Negeri 2 Tanjung Morawa which has 36 students. Kind of this research is class action Research is devided into two periods of learning. Every siclus is done a planning period, execution, observation and a reflection. Result of data analysis period I which has mark average a learning result 59,9 with classical percentage 41,66 %. Second period avarage a learning result improved becomes 76,5 with classical percentage 86,11 %, mean while an activity result on first siclus, average 11 with classical percentage 68,75 %, second siclus, everage an activity result 12,8 with classical percentage 80 % or shows that an execution of learning model make a match in learning English at class IX-5 SMP Negeri 2 Tanjung Morawa can improve an activity and the result of student learning in procedure text. Â Key Words : Students Activity, Learning Result, Make A Match, Procedure Text.